Distress and Turmoil: Learning a Language, Ego States and being-in-the-world - Latecka, Ewa (The Indo-Pacific journal of phenomenology, 2013)
This paper suggests that learning a language is accomplished through the formation of new language identities and explains this process through the use of existential phenomenology. In order for learning (and specifically, the learning of a language) to happen, a permanent change in the identity of the learner must occur. The paper suggests the introduction of the concept of linguistic ego states as a model for such a change in learner identity which, in turn, brings about the embodied (not just cognitive) retention of the acquired knowledge. In order for such retention to occur the situation must bring about anxiety, an existential crisis, or the distress and turmoil mentioned in the article’s title. This leads to a leap of faith, or an irreversible, qualitative personal change, a move to a different existential mode of being.